The Representation of Women Empowerment on The Little Mermaid Movie - Priscilla Christy Rikhana; Fanny Lesmana; Chory Angela Wijayanti (Petra Christian University, 2024)
The Little Mermaid Movie tells the story of Ariel’s journey to seek freedom and achieve her dream to be a part of the human world. This research explores the representation of women empowerment in the film using John Fiske's semiotic method, broken down into three levels, reality, representation, and ideology. The study employs a descriptive qualitative approach, with the object being the representation of women empowerment and the subject being the film The Little Mermaid. The findings reveal that the women empowerment exhibited by Ariel, the protagonist of the film, is articulated through three categories: women empowerment in making life choices, achieving equality in society, and fostering social change. These categories align with the stages of women empowerment, personal level, interpersonal level, and social action & social change. Furthermore, it is evident that the depiction of a woman with a special status, such as a double minority, can empower individuals with similar statuses who view the film. Additionally, the ideologies of revisionism and feminism are identified in the process of women empowerment depicted in the film.